Child engagement during interaction with digital and robotic activities: a systematic review - Margheri, Viola; Martucci, Alessia; Bei, Eva; Graziani, Daniela; Scatigna, Stefano; Guazzini, Andrea; Pecini, Chiara (Frontiers in Education, 2025)
IntroductionIn the last decades we assisted in the exponential increase of information and robotic technologies for remote learning and rehabilitation. Such procedures are associated with a decrease of human interaction and “in person” control of responses, characteristics that, especially when children or youth are involved, can affect learning performances. Thus, online quantitative, and qualitative indicators of child's psychological engagement are mandatory to personalize the interaction with the technological device. According to the literature, the studies on child engagement during digitalized or robotic tasks vary in terms of underpinning constructs, technological tools, measures, and results obtained.MethodsThis systematic review was conducted with the general aim to provide a theoretical and methodological framework of children's engagement during digitalized and robotic tasks. The review included 27 studies conducted between 2014 and 2023. The sample size ranged from 5 to 299, including typically and atypically developing children, aged between 6 and 18 years.ResultsThe results suggest the need for adopting a transversal approach including simultaneously emotional, behavioral and cognitive dimensions of engagement by diverse tools such as self-report questionnaires, video recordings, and eye-tracker. Although fewer studies have examined the relationship between children's engagement and task performance, existing evidence suggests a positive association between emotional, behavioral, and cognitive engagement and both task performance and skill acquisition.DiscussionThese results have implications for setting adequate protocols when using information and robotic technologies in child education and rehabilitation.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024528719, identifier CRD42024528719.